Inside Back Cover: Impacts of Dissolved Ni2+ on the Solid Electrolyte Interphase on a Graphite Anode (Angew. Chem. Int. Ed. 30/2022). Issue 30 (31st May 2022) - Xu, Hanying; Li, Zhanping; Liu, Tongchao; Han, Ce; Guo, Chong; Zhao, He; Li, Qin; Lu, Jun; Amine, Khalil; Qiu, Xinping
Abstract : The nickel–lithium ion exchange reaction in the solid electrolyte interphase (SEI) on a graphite anode is investigated by Jun Lu, Khalil Amine, Xinping Qiu, and co‐workers in their Research Article (e202202894 ). The Li + path is blocked due to the substitution of Li by Ni in the organic species, leading to the increase in the resistivity of the SEI.